Chronic Endometritis and Positive Mycoplasma Cultures: Is There a Correlation? - Ashwin Chatwani; Paul Nyirjesy; Soheil Amin-Hanjani (Hindawi Limited, 1995)
Objective: This study was undertaken to assess the impact of mycoplasma strains (Mycoplasma hominis or Ureaplasma urealyticum) on the development of chronic endometritis.